Resources Required for Internationalization of Swedish SMEs - Ehsanul CHOWDHURY; Daniella FJELLSTROM; Aihie OSARENKHOE; Sudy SUKBUA; Jane O’SULLIVAN (Communications of International Proceedings, 2023)
Aim: The aim of the study is to identify the resources required for the internationalization process for small and medium sized enterprises (SME) s in Sweden. Methodology:  A qualitative approach was used in this study where the primary data was collected from four SMEs and one industry in Sweden through five semi structured interviews. The methodology of this study follows a qualitative method wherein four SMEs were interviewed along with an industry expert. The collated data was processed according to academic procedure outlined by Creswell and Creswell (2018). Thereafter, the categorised data was analysed using an adapted situational analysis inspired by the strengths, opportunities, aspirations, resources (SOAR) Framework to identify missing resources. Findings: SMEs from Region Gävleborg, Sweden, wish to internationalise but face extensive barriers caused by the lack of necessary resources. The empirical findings align with existing literature in identifying a lack of financial, human, and intellectual resources among the SMEs. However, the findings reject theories which cited a lack of financial skills and physical resources as causal factors.  Implications of the Study:  This study adds specific insights and knowledge about the resource gaps experienced by Swedish SMEs to the literature. The outcomes indicate significant obstacles facing SMEs in the early or pre-internationalisation stage. Practical recommendations from this study suggest regional development of mentoring, accessible funding, and networking support.  Reflections on the Study and Suggestions for Future Research: The Covid-19 pandemic forced all interviews online but zoom recordings facilitated clear and accurate collection of empirical evidence. For the future, a longitudinal study of SMEs in Sweden comparing resource availability by region and/or by firm size merits investigation. Similarly, research into why the resource gaps among SMEs remain an issue would be a welcome addition to resource-based literature.
Keywords: Internationalisation; SME; Resource-based view; Sweden; SOAR Framework; Resources; Barriers.